Politik Pengelolaan Keuangan Negara (Studi Penyebab Keterlambatan Pengesahan APBA Tahun 2016) - Tgk. Zulfikar; Effendi Hasan (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2018)
ABSTRACTPost Law no. 32 of 2004, the region is given the authority to manage itsregional potential with the principle of autonomy as wide as possible. But inthe course of many raises the probation, one of them about the managementof regional finances, not least Aceh Province. The problem of financialmanagement in Aceh Province is often late for APBA approval from normallimits. The delay in APBA approval has an impact on the absorptive capacityof the budget and the availability of employment. The author's interest to dobudget research in 20016 due to political conflict between the Governor andthe DPRA. Based on the above problems, the authors are interested inassessing the causes of delay in APBA approval in 2016. The study aims todetermine the political dynamics of the 2014 APBA deliberation process andthe relation of budgetary interests of the DPRA and the Governor with thelate APBA approval in 2016 using the political theory of budget andprinciples of State / local financial management. Research uses qualitativemethods through field studies and literature. The results show that the political dynamics that occurred during the 2014 APBA deliberation process,the 2016 budget policy of the Executive dominated the Aceh DPR so that theAceh DPR's proposal was not accommodated. Miscommunication betweenthe Aceh House of Representatives and the interest of the Aceh Parliamentand the Executive. The Governor is often absent from the discussion meetingsas well as the Dyharmonization of the Governor and Vice Governor. Thedelay of APBA approval in 2016 due to deadlock discussion because there isno meeting point of interest between DPR Aceh and the Executive, theproposal is outside the authority of Aceh Government so it takes time forfinalization. Rejection of KUA-PPAS Discussion by the DPRA, theGovernment of Aceh was late applying KUA-PPAS to the Aceh DPR. It isexpected that the Governor of Aceh will be able to open the communicationroom intensively with the DPRA. To the Aceh House, it is also expected thatany budgetary policy should also consider the schedule of the budgetingcycle.Keywords: APBA Year 2016, Political Budget and Regional FinancialManagement